2005
DOI: 10.1029/2004jd005715
|View full text |Cite
|
Sign up to set email alerts
|

Precipitable water vapor on the Tibetan Plateau estimated by GPS, water vapor radiometer, radiosonde, and numerical weather prediction analysis and its impact on the radiation budget

Abstract: [1] Precipitable water vapor amounts (PW) determined by Global Positioning System (GPS), radiosonde and operational numerical weather prediction (NWP) system analysis at three stations (Naqu, Gaize, and Deqin) on the Tibetan Plateau are compared. PW measured by water vapor radiometer at Naqu and a low-elevation site, Xian, is used for calibration. The results show that the PW determined by NWP analysis in these regions is comparable with that of the radiosonde measurements but that they both are systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…In the monsoon season, the water vapor intrudes into the central and eastern TP, bringing summer precipitation. Moreover, the eastward movement of convective cloud systems developing over the TP may cause severe floods in east and southeast China (Liu et al 2005). Thus, it is very significant to monitor the amount of precipitable water vapor (PWV) and its spatial and temporal variations in this area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the monsoon season, the water vapor intrudes into the central and eastern TP, bringing summer precipitation. Moreover, the eastward movement of convective cloud systems developing over the TP may cause severe floods in east and southeast China (Liu et al 2005). Thus, it is very significant to monitor the amount of precipitable water vapor (PWV) and its spatial and temporal variations in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies showed that PWV data can be continuously derived from GPS signals according to their delays in the atmosphere with high accuracy at relatively low costs (Kuwagata et al 2001). Thus, GPS-based PWV data is often used to validate satellite-based PWV retrievals and PWV reanalysis data from numerical weather prediction models (Bock et al 2007;Liu et al 2005;Noel et al 2005). GPS-based PWV data has already been compared with AIRS PWV product in many validation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The observational technique, based on the Global Positioning System (GPS) and is sensitive to the spatial and temporal distribution of the water vapor content in the atmosphere, has made it possible to retrieve precise and continuous estimates of water vapor with spatial density governed by the number of receivers deployed (Bevis et al, 1994;Wang and Zhang, 2008). The accuracy of GPS-derived PW has been shown to be near that of measurements by a water vapor radiometer and better than that of observations from radiosonde (Liou et al, 2001;Sapucci et al, 2005;Guerova et al, 2005;Baelen et al, 2005;Liu et al, 2005;Pacione and Vespe, 2008). The advantages of GPS-derived PW include data available under all weather conditions, high temporal resolution (5-min to 2-h intervals), high accuracy (< 3 mm in PW), and long-term stability (Wang and Zhang, 2008).…”
Section: Datamentioning
confidence: 97%
“…The uncertainties of the water vapor measured by radiosonde and retrieved by Moderate-Resolution Imaging Spectroradiometer (MODIS) on the Plateau have been discussed in many studies (e.g., Takagi et al, 2000;Liu et al, 2005Liu et al, , 2006. Lack of precise and continuous water vapor observations is one of the major sources of error in numerical weather prediction models (Liu et al, 2005).…”
Section: Datamentioning
confidence: 99%
“…Atmospheric water vapour only accounts for a small proportion of total atmospheric volume, but it plays an important role in the formation of clouds and rainfall, as well as the evolution of weather systems (Liu et al, 2005;Wang et al, 2014). Knowing precise information about the spatiotemporal distribution of water vapour is a prerequisite for atmospheric research (Emanuel et al, 1995;Park et al, 1999;Bauer et al, 2011;Ducroco et al, 2002).…”
Section: Introductionmentioning
confidence: 99%